Iron-containing nanocomposites based on humic substances and their biological activity (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Research relevance: biological activity is one of the most important properties of nanocomposites. Nanocomposites based on hectorite and humic substances are iron-containing nanocomposites combined with organic macromolecules, exhibiting numerous properties and high structural complexity, which can be applied in biomedicine as diagnostic and therapeutic tools. Therefore, studying the bioactivity of nanocomposites based on hectorite and humic substances is a relevant research direction. Objectives of the study based on the study of biological activity of nanocomposites based on hectorite and humic substances. Mechanisms of formation of hectorite nanocomposites with organic substances were determined. Research results: interactions between water-soluble humic acids (HA) and Fe(oxy)hydroxides (α-FeOOH, α-Fe₂O₃, polymerized amorphous iron phases) were studied. The mechanisms of formation of hectorite nanocomposites with organic substances were identified. Iron oxides strongly interact with the negative surface charge of humic acids. Nanohybrid composites of hectorite (α-FeOOH) with carbon-containing organic substances (activated carbon, humic acids) have been obtained. The toxicity of these synthesized iron-containing preparations was determined, and their biological activity was investigated.
Keywords: biological activity, nanocomposites, goethite, humic substance, iron oxide, humic acids, structure, phase